Linking energy behaviour, attitude and habits with environmental predisposition and knowledge. Issue 4 (21st April 2017) - Pothitou, Mary; Varga, Liz; Kolios, Athanasios J.; Gu, Sai
Abstract : The purpose of this paper is to present and discuss the findings of an empirical study that compares individuals' environmental predisposition and knowledge with their energy behaviour, attitude and habits. Additionally, the study attempts to correlate education level and household income with the above variables. The statistical analysis reveals significant correlations between environmental predisposition and knowledge and elements of individuals' energy attitudes, habits and behaviour. An unanticipated outcome from the principal component analysis was that household income, and to a lesser extent gender, is associated with energy-saving habits and behaviours. On further investigation, household income was found to be correlated with knowledge of greenhouse gas emissions and the number of laptops and electric showers owned per household. The study sample comprises 68 employees of an educational institution, which was selected as the first phase of research aiming to compare energy-saving behaviour at home and in the workplace.